Casca de café melosa ensilada na alimentação de suínos - Carvalho, Paulo Levi de Oliveira (2008)
Four experiments were carried out to determine the nutritional value and to verify the performance of starting, growing and finishing pigs fed with sticky coffee hull silage (SCHS). In the Experiment I, a digestibility trial, was carried out using fifteen cross breed barrow with initial body weight of 20.78 ± 2.86 kg in metabolism cages, allotted in a completely randomized design. The evaluated feeds were sticky coffee hull (SCH) and SCHS. In general, the process of ensilage did not improve the SCHS digestibility. The values of DE, as fed basis, obtained for SCH and SCHS, were 2,352 and 1,605 kcal/kg, respectively. In the Experiment II, 60 piglets (30 barrows an 30 female) were used, initial body weight 15.52 ± 2.29 kg, allotted in a completely randomized design, with five treatments, six replicates and two pigs per pen (experimental unit). The treatments consisted of five diets with increasing levels (0, 4, 8, 12 and 16%) of SCHS. There were no effects of SCHS inclusion on daily fed intake, daily weight gain, feed:gain ratio and plasma urea nitrogen. The study of economic viability indicated the possibility of SCHS inclusion to 4%. It is concluded that SCHS presents good nutritional value and can be included up to 16% in nursery piglets (15-30 kg) diets without impairing performance, however the feasibility of using SCHS, will depend of feedstuffs prices. In the Experiment III, a digestibility trial were carried out using fifteen cross breed barrow with initial body weight of 43.06 ± 4.12 kg allotted in metabolism cages, in a completely randomized design. The evaluated feeds were sticky coffee hull (SCH) and SCHS. The ensilage process did not improve the digestibility of SCHS. The values, as fed basis, of DE obtained for SCH and SCHS, were 2,143 and 1,431 kcal/kg, respectively. In the Experiment IV, 60 pigs (30 male an 30 female) were used, initial body weight of 32.52 ± 3.21 kg in growing phase and 55 pigs, with initial body weight of 61.70 ± 3.29 kg, in finishing phase, allotted in a completely randomized design with five treatment, six replicates and two pigs per pen (experimental unit). The treatments consisted of five diets with increasing levels (0, 4, 8, 12 and 16%) of SCHS. In the growing phase there were no effect of inclusion levels of SCHS on daily fed intake, daily weight gain, feed:gain ratio and plasma urea nitrogen. The study of economic viability indicated the possibility of SCHS inclusion up to 8%. In the finishing phase, the feed:gain ratio showed a improved with the increasing SCHS inclusion levels. The daily fed intake, daily weight gain and plasma urea nitrogen and loin depth did not differ between SCHS inclusion levels, however the economic viability indicated the possibility of SCHS inclusion up to 8%. The results of carcass traits indicated a quadratic effect on backfat thickness and marbling score of the longissimus dorsi. There was a linear increasing on weight of empty stomach according to the addition of SCHS on diets. These results suggest that SCHS presents good nutritional value and can be included up to 16% in starting, growing and finishing pigs diets, without impairing performance and carcass traits, however the feasibility of using SCHS, will depend of feedstuffs prices.